PEMANFAATAN PISANG SEBAGAI VARIASI MENU SEHAT - S.I Trahutami; Reny Wiyatasari (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
Bananas are one of the fruits in tropical countries that have quite high social and economic value. In addition to its good taste and high vitamin A content and calories, bananas are widely used in a variety of foods by most Indonesian people. The purpose of this activity is to offer a variety of banana-based snacks or healthy menus through training on making banana nuggets. This service’s activity to society was carried out with a simulation method, namely the practice of making banana nuggets involving housewives and young women with a limited amount.Keywords : Bananas, healthy menus, banana nuggets